Functional Trimeric SARS-CoV-2 Envelope Protein Expressed in Stable CHO Cells - Mayrhofer, Patrick; Hunjadi, Monika; Kunert, Renate (Frontiers in Bioengineering and Biotechnology, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a β-coronavirus, is the causative agent of the COVID-19 pandemic. One of the three membrane-bound envelope proteins is the spike protein (S), the one responsible for docking to the cellular surface protein ACE2 enabling infection with SARS-CoV-2. Although the structure of the S-protein has distinct similarities to other viral envelope proteins, robust and straightforward protocols for recombinant expression and purification are not described in the literature. Therefore, most studies are done with truncated versions of the protein, like the receptor-binding domain. To learn more about the interaction of the virus with the ACE2 and other cell surface proteins, it is mandatory to provide recombinant spike protein in high structural quality and adequate quantity. Additional mutant variants will give new insights on virus assembly, infection mechanism, and therapeutic drug development. Here, we describe the development of a recombinant CHO cell line stably expressing the extracellular domain of a trimeric variant of the SARS CoV-2 spike protein and discuss significant parameters to be considered during the expression and purification process.